2001
DOI: 10.1002/1521-4184(200110)334:10<332::aid-ardp332>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive properties of chalcones. Structure-activity relationships

Abstract: Eleven chalcones were prepared and tested as antinociceptive agents using the writhing test in mice. Some compounds, given intraperitoneally, caused potent and dose‐related antinociception, being several times more active than some reference drugs. The results evidenced that some physico‐chemical parameters are involved in the pharmacological activity. 3,4‐Dichlorochalcone (2) was the most effective compound, and was also studied in another model of pain in mice, the formalin test. Here it inhibited only the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 11 publications
1
5
0
2
Order By: Relevance
“…We were not able to determine the opioid receptors involvement in the antinociceptive activity of those pure compounds because the amount yielded was not enough for further studies. In term of chalcones, several reports have demonstrated that this class of compounds exhibited antinociceptive activity [2830] even when assessed using the formalin test [30, 31]. Further preparations of extract and partitions for the isolation of those compounds are currently being carried out in our laboratory with hope of using them to study the possible mechanisms of antinociception involved.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to determine the opioid receptors involvement in the antinociceptive activity of those pure compounds because the amount yielded was not enough for further studies. In term of chalcones, several reports have demonstrated that this class of compounds exhibited antinociceptive activity [2830] even when assessed using the formalin test [30, 31]. Further preparations of extract and partitions for the isolation of those compounds are currently being carried out in our laboratory with hope of using them to study the possible mechanisms of antinociception involved.…”
Section: Discussionmentioning
confidence: 99%
“…A LC24 apresenta o substituinte metoxi na posição 4', sendo descrito na literatura que a presença do grupo metóxi em posição para é capaz de aumentar a atividade anti-inflamatória por inibição da COX (BANO et al, 2013). A presença de grupos retiradores de elétrons no anel ligado diretamente à carbonila, como o substituinte cloro na posição 2' na LC41, está relacionado com o aumento do efeito antinociceptivo em modelos de dor aguda pelo teste da formalina e teste de contorções abdominais (CORRÊA et al, 2001). Além disso, também é atribuído ao grupamento nitro uma atividade complementar para inibição da COX-2 (BUKHARI et al, 2012), sendo este grupamento presente na LC41 na posição 4 do anel aromático ligado ao carbono beta da função olefínica.…”
Section: Gruposunclassified
“…Inúmeras técnicas têm sido descritas para síntese de chalconas, dentre estas se destaca o método de Claisen-Schmidt, que consiste na reação de uma acetofenona com um aldeído aromático (BUKHARI; JASAMI; JANTAN, 2012). Muitas chalconas e seus derivados sintéticos possuem a capacidade de inibir as principais vias pró-inflamatórias, e apresentam atividades antinociceptiva e anti-inflamatória (CORRÊA et al, 2001;ROJAS et al 2002;WON et al, 2005;MOHAMAD et al, 2010;JANTAN et al, 2014;ISMAIL et al, 2016;STAURENGO-FERRARI et al, 2018;UR RACHID et al, 2019).…”
Section: Introductionunclassified
“…The data set used for the 2D QSAR analyses contains 34 analgesic cyclic imides, which have been selected from the literature [17][18][19][20][21][22][23]. The structures and corresponding pID 50 values (-log ID 50 , where ID 50 corresponds to the dose of compound that reduced responses by 50% relative to control value) for the whole set of compounds are included in Table 1.…”
Section: Data Setmentioning
confidence: 99%